The yield of sweet and green corn consumed "in natura" (unprocessed) cultivated in Tocantins (Research, Society and Development, 2021)
Corn (Zea mays L.) belongs to the Poaceae family, stands out for its great genetic diversity, adapting in different climates. This study aims to study the yield of green and sweet corn grown in Tocantins. The experiments were carried out at the Federal University of Tocantins - UFT, Palmas's Campus and Federal Institute of Tocantins - IFTO, Paraiso's Campus, where 4 corn cultivars were planted (C1, C2 and C3 of common green corn and C4 of sweet corn), on different environments, fertilization levels and sowing times. The yield green grains of C4 were similar (p